MOLE: a Voronoi diagram-based explorer of molecular channels, pores, and tunnels - Petřek, Martin; Košinová, Pavlína; Koča, Jaroslav; Otyepka, Michal (Structure, 2007)
We have developed an algorithm, "MOLE," for the rapid, fully automated location and characterization of molecular channels, tunnels, and pores. This algorithm has been made freely available on the Internet (http://mole.chemi.muni.cz/) and overcomes many of the shortcomings and limitations of the recently developed CAVER software. The core of our MOLE algorithm is a Dijkstra's path search algorithm, which is applied to a Voronoi mesh. Tests on a wide variety of biomolecular systems including gramicidine, acetylcholinesterase, cytochromes P450, potassium channels, DNA quadruplexes, ribozymes, and the large ribosomal subunit have demonstrated that the MOLE algorithm performs well. MOLE is thus a powerful tool for exploring large molecular channels, complex networks of channels, and molecular dynamics trajectories in which analysis of a large number of snapshots is required.
Keywords: Crystallography, X-Ray; Proteins; Software; Protein Conformation; Databases, Protein; software; proteiny; Algorithms; konformace proteinů; Ion Channels; molekulární modely; databáze proteinů; Models, Molecular; algoritmy; iontové kanály; krystalografie rentgenová